2009
DOI: 10.1016/j.homp.2008.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte proliferation stimulated by activated human macrophages treated with Canova

Abstract: In this study, the MI of lymphocyte cultured received the medium containing CA-stimulated macrophages showed a higher proliferation index (p<0.01) than the lymphocytes cultured in a medium without CA-treated macrophages. Our results suggest that CA treatment, in addition to activating macrophages, indirectly induces lymphocyte proliferation and has potential as a new adjuvant therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 8 publications
2
15
1
Order By: Relevance
“…Our group also previously observed that CA induces macrophage activation and indirectly leads to lymphocyte proliferation in vitro [1] . CA activated macrophages present an increase in the intracellular activity of the NAD(P)H oxidase and Nitric Oxide Sintetase (NOS) enzymes, therefore stimulating the production of reactive oxygen species (ROS) and nitric oxide, which might induce gene expression and/or protein modification that are likely to be an alternative signaling pathway to activate other macrophages, favoring the immune response [9] .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our group also previously observed that CA induces macrophage activation and indirectly leads to lymphocyte proliferation in vitro [1] . CA activated macrophages present an increase in the intracellular activity of the NAD(P)H oxidase and Nitric Oxide Sintetase (NOS) enzymes, therefore stimulating the production of reactive oxygen species (ROS) and nitric oxide, which might induce gene expression and/or protein modification that are likely to be an alternative signaling pathway to activate other macrophages, favoring the immune response [9] .…”
Section: Discussionsupporting
confidence: 58%
“…CA activates macrophages both in vivo and in vitro and indirectly induces lymphocyte proliferation [1] . Experiments in vivo and in vitro point out that treatment with CA can cause tumor size reduction and regression in animals, and can also recover cells viability after they were damaged [2] .…”
Section: Introductionmentioning
confidence: 99%
“…It is a complex homeopathic immunomodulator indicated for patients whose immune system is depressed. Canova activates macrophages both in vivo and in vitro and indirectly induces lymphocyte proliferation [6]. Since innate and adaptive immune responses play a role in tumor surveillance and clearance [7], enhancing the ability to trigger a specific immunologic response against malignant cells is an important anticancer approach.…”
Section: Introductionmentioning
confidence: 99%
“…159,247249 Adaptive changes in allostasis initiated by low dose nanoparticles during homeopathic treatment could help restore more normal balance between pro- and anti-inflammatory cytokines, as suggested by previous studies. 6669,163,182,185,250–252 The result would be improvements of both psychological and physical well being across a wide range of conditions, as is claimed in hundreds of anecdotal case reports from homeopaths and supported by a number of observational trials. 253,254 …”
Section: The Net Clinical Outcome Of the Simillimum Remedy Interactiomentioning
confidence: 91%